Audit Sistem Informasi Instlasai Rawat Inap Berdasarkan Prespektif Pelanggan Balanced Scorecard Menggunakan Standar COBIT 4.1 (Studi Kasus: Rumah Sakit Umum Haji Surabaya) - Dhipiya, Finh Yutta; Tanuwijaya, Haryanto; Sutomo, Erwin (Jurnal JSIKA, 2012)
RSU Haji Surabaya has a Information System Management (SIM-RS) unit which control information system on inpatient unit. This system are used to handle public customer in cooperation with third party vendor. There are several activity on this vacility such as, patient registration, serving the patient, patient medical record and patient treatment cost detail. There are never audit activity ever held on inpatient vacility to make sure IT goal and business goal alligment. This paper describe how audyt information system are applied in inpatient vacility to assess information system performance. The company are helding audit information system based on COBIT 4.1 standart to assess business process, application and business strategic allignment. COBIT 4.1 was chosen as a standart on information audit for it´s exellence on IT control along with providing framework to assess IT performance as an object. Another, the audit are focused on customer perspective of balanced scorecard. The results of this audit states that the maturity level of 3.21,which is defined. This means that the procedure on the purpose of acquiring businesses that are useful and reliable information for strategic decision making has been standardized and documented, and communicated through training. but its implementation still depends on the individual whether to follow the procedure or not. The procedure was developed as a formalization of existing practice. Keywords: Information System, Information Systems Audit, Customer Perspective, The Balanced Scorecard, COBIT, Maturity Level